The Study of the Release Mechanism of TiO2 Nanotubes-NP Conjugate Using Polymer Encapsulate as a Drug Delivery System - Mohammed, Asma Hadi; Hasan, Basim M; Al-Hashimy, Wisam Khadom; Khalaf, Majid Shannon (Al-Nahrain Journal of Science, 2016)
TiO2 nanotube array was fabricated by anodisation technique of a pure titanium plate. The anodisation process was carried out in ammonium fluoride/ ethylene glycol electrolyte, the applied voltage was 60 volt. The average length and diameter of the nanotubes were 12 µm and 80 nm respectively. After annealing of TiO2 nanotubes at 500°C for 3h, the amorphous nanotubes walls converted into anatase phase. The TiO2 nanotubes array material was employed as container for methylene blue (MB) solution. Another layer (container for MB) was created then when TiO2 coated with nanoparticles (NP) in order to compare the release mechanism with TiO2 nanotubes. The aim was to develop an additional control of chemical release kinetics polyvinyl alcohol (PVA) which was used to encapsulate the surface of the loaded TiO2 nanotubes and TiO2 nanotubes-NP conjugate. The results showed that the release mechanism can be controlled more efficiently by using nanotubes-NP conjugate rather than using single layer of TiO2 nanotubes only. The morphology of the arrays was characterized by X-ray diffraction (XRD), Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM).